PANCASILA SEBAGAI LANDASAN IDEOLOGI DALAM PRAKTIK MODERASI BERAGAMA DI INDONESIA - Nanang Jainuddin (CV. ADIBA AISHA AMIRA, 2023)
This research discusses the role of Pancasila as an ideological foundation in the practice of religious moderation in Indonesia. As a country with various ethnicities, religions and cultures, Indonesia faces complex challenges in maintaining social harmony. This pluralism has both positive and negative impacts on society. In this context, religious moderation is an important approach to maintaining religious diversity in harmony. Pancasila, as the state ideology, has values that support the practice of religious moderation, with a focus on inclusivity, tolerance and interfaith dialogue. Conformity between Pancasila values and the principles of religious moderation in creating harmony is carried out through the integration of Pancasila values with the principles of religious moderation. This forms the basis of peaceful, inclusive and harmonious religious practice in a diverse society. Steps towards the future to integrate more firmly the values of Pancasila in the development of religious moderation in Indonesia involve the role of educational institutions and the media. Educational institutions can play an important role in shaping an open and inclusive attitude in the younger generation, while the media can promote Pancasila values and religious moderation to the wider community. Pancasila as the basic ideology of the state supports the practice of religious moderation in Indonesia and can be used in facing the challenges of radicalism and extremism